Synergistic Ability of Tannin – Silica as a Corrosion Inhibitor with the Addition of KI to Mild Steel in Demineralized Water - Arief, Hendra; Pramudita, Marta; Pitaloka, Alia Badra (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2023)
The rapid industrial growth in Indonesia today requires effective and efficient operating and maintenance conditions. The application of corrosion protection in cooling towers and boilers shows that inhibitor materials such as nitrates, nitrites and chromates must be used in large concentrations; these inhibitors also cause environmental pollution. For this reason, bio-inhibitors derived from natural ingredients have begun to be developed. Tannins and silica are widely known as effective inhibitors in controlling carbon steel corrosion. The synergistic mechanism of inhibitors is known to increase the effectiveness of inhibitory substances. This study aims to study the effectiveness and understand the mechanism of tannin and silica inhibitors and the effect of adding potassium iodide. as a synergistic inhibitor. This study used samples of mild steel carbon steel with demineralized water media at a temperature variation of 30-60oC and immersion time of 1, 2 and 3 hours. Variations in the concentration of tannins and silica used are 0-1250 ppm, and the corrosion measurement method uses the weight loss method. The results showed that adding potassium iodide. They have increased the ability of mild steel corrosion inhibitors produced by tannin-silica synergy. The corrosion rate of mild steel can be reduced by 82.95% at a concentration of tannin-silica-KI 1250 ppm. Therefore, tannin-silica synergy with the addition of potassium iodide. It has the potential to be a good alternative in the use of corrosion inhibitors for mild steel in demineralized water.